A study on parents support and participation in their children's educational achievement / Nelly Sylvester Basayu - Sylvester Basayu, Nelly (2009)
This study conducted for 50 respondents at Kampung Penampang Proper for the purpose to see the level of parents support and participation and to examine the factors associates with the parents support and participation in their children's educational achievement. From the findings that have been conducted by using descriptive and Spearman's test analysis, it shown that most of parents do aware and concern about their children's educational achievement and the factors that are vital towards parents support and participation are parent's responsibility, communication between parents and children and supporting learning at home. Parents reported that their responsibility, communication between parents and children and supporting learning at home played important factors that they should maintain and sustain continuously in order to ensure that their children's success academically in present and future time.